Advanced thermochemical resorption heat transformer for high-efficiency energy storage and heat transformation. (15th May 2019) - Wu, S.; Li, T.X.; Yan, T.; Wang, R.Z.
Abstract: Thermochemical heat transformer based on reversible chemical reaction can combine the heat transformation and storage to realize the high-efficiency utilization of thermal energy. In this paper, an advanced thermochemical resorption heat transformer prototype was designed for the first time to verify a basic thermochemical resorption cycle which can achieve the amplification of available heat in quantitative terms. The working pairs of MnCl2 /NH3 -SrCl2 /NH3 were employed and expanded graphite served as the additive to synthesize composite sorbents with enhanced heat and mass transfer performance. The thermodynamic analysis based on the coupled relationship of temperature and pressure was firstly carried out. The system performances including energy efficiency, heating power and storage density were investigated. The experimental results showed that the maximum coefficient of amplification and energy storage density reached 1.74 and 444.1 kJ/kg composite sorbent without consideration of sensible heat under the operation conditions of the heat source temperature of 120 °C −150 °C, heat output temperature of 50 °C and ambient temperature of 30 °C. The heating power of the prototype in the charging phase increased with the increment of heat source temperature and its maximum value reached 2057 W. Further discussion on extending the working temperature range was completed and the potential application was analyzed. It was proved that the heat transformer prototype could realize the high-efficiency utilization of the intermittent high/medium grade heat by achieving the continuity of heat supply in time terms and amplification of available heat in quantitative terms. Highlights: An advanced solid-gas thermochemical resorption heat transformer is developed. The thermodynamic analysis based on coupled relationship of T and P is carried out. The maximum COA and energy density reach 1.74 and 444.1 kJ/kg composite sorbent. The heating power in the charging phase varies from 500 to 2057 W. The heat transformer can realize the high-efficiency utilization of thermal energy.